Copper/Graphene Based Materials Nanocomposites and their Antibacterial Study: A Mini Review - Ismail , Nur ‘Afini; Shameli, Kamyar; Rasit Ali, Roshafima; Mohamad Sukri, Siti Nur Amalina; Mohamed Isa, Eleen Dayana (Journal of Research in Nanoscience and Nanotechnology, 2021)
Due to their biocidal activity properties, graphene based materials have been widely studied especially in biomedical, agriculture and water treatment process which focus on mitigating the microbial resistance problem. However, the antibacterial performance of these materials alone are relatively weak and need to be improved in order to enhance their biological activity. Copper nanoparticles is a low cost metal also has the antibacterial properties which is almost similar with the silver and gold nanoparticles. The combination of these two materials had produced to a new potential material as another alternative for the antibacterial agents. Therefore, in this work, a brief review of copper/graphene based material nanocomposites and their antibacterial study was discussed.